2010
DOI: 10.1177/1934578x1000500130
|View full text |Cite
|
Sign up to set email alerts
|

Essential Oil Composition of Achillea clusiana from Bulgaria

Abstract: The essential oil compositon of Achillea clusiana Tausch from Bulgaria has been studied by GC and GC/MS. Fifty-four components were registered, representing 92.5% of the oil. The oil was characterized by the presence of oxygenated mono- and sesquiterpenoids. The main components were β-thujone (17.2%), 1,8-cineole (11.2%), camphor (11.1%) and α- thujone (7.8%). Farnesol (3.1%), nerolidol (2.7%) and oxygenated nerolidol derivatives (cabreuva oxides A-D, isohumbertiols A-D, bejarol and 7-hydroxy-6,7-dihydro-5,6E-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…The various effects of these plants may be due to the presence of a broad range of secondary metabolites such as flavonoids, phenolic acids, lignans, amino acid derivatives, terpenoids and sterols [7]. The genus Achillea has a complex taxonomy, and studies on the composition of the essential oils have been used as an additional characteristic of inter-and infra-specific differentiation [8][9][10]. However, the existence of chemical variability concerning yarrow essential oil composition seems to be a well-known phenomenon.…”
mentioning
confidence: 99%
“…The various effects of these plants may be due to the presence of a broad range of secondary metabolites such as flavonoids, phenolic acids, lignans, amino acid derivatives, terpenoids and sterols [7]. The genus Achillea has a complex taxonomy, and studies on the composition of the essential oils have been used as an additional characteristic of inter-and infra-specific differentiation [8][9][10]. However, the existence of chemical variability concerning yarrow essential oil composition seems to be a well-known phenomenon.…”
mentioning
confidence: 99%
“…fascicularis (33%), Piper hispidum (23.6%), cucumber tree (20%), and orange jessamine (25.7%) . Noticeable content of nerolidol was also reported in the composition of volatiles of an enormous number of essential oils, a modest example of which would be the following reports …”
Section: Introductionmentioning
confidence: 99%
“…Terpenoids (1,8-cineole, camphor, bomeol, pinenes, artemisia ketone, santolina alcohol, farnesane, caryophyllene and its oxides, -bisabolol and oxides, cubebene, germacrenes, eudesmol, farnesene, -gurjunene, -muurolene and chamazulene) are the principle components of Achillea essential oils [3,4]. Yarrow's healing power is mainly attributed to proazulenes, and so the chemical composition of yarrow oils has been investigated by several research groups in different countries [4,6,8,10,11] Piperitone was a major constituent of sample C (10.9%), but was not detected in the other four samples ( Table 2). Sample E was collected from Isparta in southwestern Turkey, and its chemical profile was similar to that of sample D; 1,8-cineole (34.3%), camphor (21.7%) and p-cymene (13.4%) were the main components.…”
mentioning
confidence: 99%
“…Phytochemical studies carried out on Achillea essential oils have identified sesquiterpene lactones, flavonoids, alkaloids, lignans, triterpenes alkamides and polyacetylenes [3,4]. Achillea essential oils and sesquiterpene lactones have been studied by a number of investigators, but never evaluated for their potential as agrochemicals [3,4,8,10,11]. Terpenoids (1,8-cineole, camphor, bomeol, pinenes, artemisia ketone, santolina alcohol, farnesane, caryophyllene and its oxides, -bisabolol and oxides, cubebene, germacrenes, eudesmol, farnesene, -gurjunene, -muurolene and chamazulene) are the principle components of Achillea essential oils [3,4].…”
mentioning
confidence: 99%
See 1 more Smart Citation